Canadian Thoracic Society 2011 Guideline Update: Diagnosis and Treatment of Sleep Disordered Breathing - John Fleetham; Najib Ayas; Douglas Bradley; Michael Fitzpatrick; Thomas K Oliver; Debra Morrison; Frank Ryan; Frederic Series; Robert Skomro; Willis Tsai; The Canadian Thoracic Society Sleep Disordered Breathing Committee (Canadian Respiratory Journal)
The Canadian Thoracic Society (CTS) published an executive summary of guidelines for the diagnosis and treatment of sleep disordered breathing in 2006/2007. These guidelines were developed during several meetings by a group of experts with evidence grading based on committee consensus. These guidelines were well received and the majority of the recommendations remain unchanged. The CTS embarked on a more rigorous process for the 2011 guideline update, and addressed eight areas that were believed to be controversial or in which new data emerged. The CTS Sleep Disordered Breathing Committee posed specific questions for each area. The recommendations regarding maximum assessment wait times, portable monitoring, treatment of asymptomatic adult obstructive sleep apnea patients, treatment with conventional continuous positive airway pressure compared with automatic continuous positive airway pressure, and treatment of central sleep apnea syndrome in heart failure patients replace the recommendations in the 2006/2007 guidelines. The recommendations on bariatric surgery, complex sleep apnea and optimum positive airway pressure technologies are new topics, which were not covered in the 2006/2007 guidelines.